Enhancing Green Banking Practices to Support Sustainable Development Goals: A Case Study of Bank Syariah Indonesia in Purwokerto - MEI, Ubaidillah; Akhris Fuadatis Solikha; Putri Khoirunnisa Azahra (Journal of Finance and Islamic Banking, 2024)
Green banking policies are crucial in aligning banking practices with environmental sustainability and supporting the global agenda of Sustainable Development Goals (SDGs). However, the implementation of such policies, particularly in Islamic banking institutions in Indonesia, remains underexplored. This study examines the implementation of Green Banking policies at Bank Syariah Indonesia in Purwokerto and assesses customer perceptions of these policies. Using a qualitative approach with field research methods, data were collected from Bank Syariah Indonesia employees, the Financial Services Authority (OJK), the Ngudi Dadi Livestock Group, customers, and MSMEs in Banyumas. Data analysis utilized the Miles and Huberman model with validation through the Triangulation method. The results reveal that Bank Syariah Indonesia has implemented Green Banking through Defensive, Preventive, Offensive, and Sustainable Banking approaches. Additionally, the application of the Green Coin Rating (GCR) framework—including carbon emissions reduction, green rewards, green building initiatives, recycling practices, paperless operations, and green investments—contributes to achieving the SDGs. These findings address research gaps and emphasize the policy's contributions to sustainability and customer engagement.